New technique for the cure of urinary incontinence in women. - Guillén Araoz, Félix (2015)
In this paper the results are presented by the surgical treatment of urinary incontinence in women using the Marshall-Marchetti Modified technique compared with the original technique Marshall-Marchetti-Krantz, the results are evaluated and some concepts are mentioned on urinary incontinence.